Banking-finance in the Tourism Sector of Bangladesh: Prospects and Challenges - Md Matiur Rahman; Samia Tahsin (CenRaPS Journal of Social Sciences, 2020)
This paper aims to add to this thrust of discussion on the prospect of Bangladesh in terms of tourism highlighting the connections between banking and finance towards its advance. However, the government of Bangladesh has planned for an efficient and sustainable economy model than garments export, the tourism sector could make a highly significant contribution to improving the growth prospects of Bangladesh particularly in terms of GDP, employment generation and foreign exchange earnings. When looking into the direction in banking and financial services, the resumes found remarkable feasibility that can be cardinal for tourism dissection though its investment, employment generation and foreign exchange earnings. However, the following are some of the challenges that are still prevailing regarding banking and finance incorporated in the tourism industry. The limitation of infrastructure is still an area of concern, the problem of regulation and policies is also another problem area to be considered and lastly the realization that there is need for construction of policies to foster the right strategic directions. Based on the identification of the above challenges, this study aims at producing the solutions in terms of policy options for policymakers, financial institutions, and other relevant stakeholders in order to address the challenges of tourism-related financial activities in the development of these sectors. Therefore, the current article extends the understanding about the banking and finance function and contribution in the context of tourism of the Bangladesh boosting from the improved qualitative review of the literature along with quantitative data and the experience & revelation of the authors. It enables the individual to learn some of the influential trends in the country, not just the perceived opportunities and threats which the nation may face while aiming at promoting the economic potential of the developing tourism industry. The outcomes of the presented study are intended to help forming evidence-based best practices for further developments that would strengthen the financial platform for positive tourism expansion in Bangladesh.